PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI BULLYING VERBAL DI SEKOLAH MENENGAH PERTAMA - Laily, Laily Puji Astuti (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
The main role of guidance and counseling teachers is expected to be able to overcome verbal bullying in junior high schools. One of the functions of guidance and counseling refers to Permendikbud number 111 of 2014, guidance and counseling in repair and healing, namely helping students with problems to correct mistakes in thinking, feeling, willing and acting. Guidance and counseling teachers must be able to: 1) be able to prioritize the welfare of clients, 2) develop competence in clients' cultural diversity skills, 3) develop information processing and emotional control skills, 4) have high resilience in facing problems. The role of guidance and counseling teachers is an effort to prevent and overcome verbal bullying in schools to provide good and comprehensive counseling to all students using skills to help create guidance and counseling services. The function of guidance and counseling can help students overcome problems, be able to make their own and independent decisions and obtain change and better direction. Therefore, the role of guidance and counseling teachers in schools is very important in serving junior high schools. So that counselors have the ability to understand the characteristics of students who can provide good counseling..